The Forever Dog Life : over 120 recipes, longevity tips, and new science for better bowls and healthier homes - Becker, Karen Shaw; Habib, Rodney; Durand, Sarah (New York, NY : Harper, an imprint of HarperCollins Publishers, 2024)
"In this guide, the authors of the #1 internationally bestselling The Forever Dog show how to create a healthy, sustainable lifestyle and environment to help your dog live a longer, happier, and healthier life"--.
new book 2024 summer.
Includes bibliographical references and index.
Keywords: Dogs -- Food; Dogs -- Food -- Recipes; Dogs -- Health; Dogs -- Aging